An Analytical Study of Self-Compensating Dynamic Balancer with Damping Fluid and Ball - Jongkil Lee (Shock and Vibration)
The self-compensating dynamic balancer (SCDB) is composed of a circular disk with a groove containing ball and a low viscosity damping fluid. The equations of motion of the rotating system with SCDB were derived by the Lagrangian method. To consider dynamic stability of the motion, perturbation equations were investigated. Based on the results of stability investigation, ball positions that result in a balanced system are stable above the critical speed with small damping (β′>3.8 case). At critical speed the perturbed motion is said to be stable for large damping (β′>2.3 case). However, below critical speed the balls cannot stabilize the system in any case.